Tooth allotransplantation: Evaluation and report of 15 cases - AH. Fakhraie; E. Yazdi; M. Falahi Motlagh (Tehran University of Medical Sciences, 1994)
Tooth Transplantation from one individual to another is a method of replacing missing teeth. This method can be used as an applicable clinical treatment technique due to its numerous advantages .There are different methods of tooth transplantation. Among those, the safest and healthiest is transplantation of non-vital teeth or allostatic transplantation. In this method, the risk of antigenicity in recipient is low and also there is no risk of transmission of infectious diseases such as Hepatities or AIDS. The aim of this study was to evaluate the clinical results of tooth allotransplantation. Current study was conducted on 15 non-vital transplanted teeth within 18 months follow-up. Only one case of rejection was observed which was a Traumatic Rejection. Replacement resorption was found in all the cases while inflammatory resorption was recorded in only two cases. WBC Cross Match Test with pannel cell results were negative in all the cases.